2018
DOI: 10.1051/0004-6361/201832830
|View full text |Cite
|
Sign up to set email alerts
|

From interstellar carbon monosulfide to methyl mercaptan: paths of least resistance

Abstract: The 29 reactions linking carbon monosulfide (CS) to methyl mercaptan (CH 3 SH) via ten intermediate radicals and molecules have been characterized with relevance to surface chemistry in cold interstellar ices. More intermediate species than previously considered are found likely to be present in these ices, such as trans-and cis-HCSH. Both activation and reaction energies have been calculated, along with low-temperature (T > 45 K) rate constants for the radical-neutral reactions. For barrierless radical-radica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…To obtain branching ratios for radical-radical reactions considered in the reaction network, an approach similar to that used in Lamberts (2018) was employed. In particular, we took the approach to run geometry optimizations for structures where the two radicals are placed in a random orientation with respect to each other.…”
Section: Electronic Structure Calculations To Determine the Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain branching ratios for radical-radical reactions considered in the reaction network, an approach similar to that used in Lamberts (2018) was employed. In particular, we took the approach to run geometry optimizations for structures where the two radicals are placed in a random orientation with respect to each other.…”
Section: Electronic Structure Calculations To Determine the Branchingmentioning
confidence: 99%
“…The ChemShell framework was used for all calculations (Sherwood et al 2003;Metz et al 2014), using Turbomole (Ahlrichs et al 1989;Treutler & Ahlrichs 1995) and DL-Find (Kästner et al 2009) for the geometry optimizations. For radical-radical reactions it is crucial to use an unrestricted broken-symmetry wave function with overall as many spin-up as spin-down electrons, but finite spin density on both radicals (e.g., Lamberts (2018); Enrique-Romero et al (2019)). No Hessian calculations were performed.…”
Section: Electronic Structure Calculations To Determine the Branchingmentioning
confidence: 99%
“…In conclusion, we presented an optimized method for efficient gas-phase generation of the simplest organosulfur radical CH 3 S• (2) in the gas phase, opening the door to further studies on its structure and reactivity, particularly on its diverse reactions involving in Earth's atmosphere and also the potent involvement in the astrochemistry of merthyl mercaptan (CH 3 SH) that has been recently detected in the interstellar medium (ISM) [64][65][66] . In addition to the first time identification of the characteristic absorption at 375 nm in the UV-vis spectrum of 2, its photoinduced (365 nm) sulfur atom transfer SAT to molecular nitrogen has been observed in an N 2 -matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the prospective detection of trans/cis thiohydroxycarbene, which have dipole moments of 1.8 and 2.6 Debye, respectively (33), would be invaluable to test future chemical models of the organosulfur chemistry in star-forming regions. In terrestrial laboratories, all previous attempts to detect trans/cis-thiohydroxycarbene spectroscopically in the gas phase or in low-temperature matrices were unsuccessful, although Lamberts suggested that thiohydroxycarbene should represent a reactive intermediate in the hydrogenation of carbonyl monosulfide (CS) on interstellar grains (44). The high reactivity, even in lowtemperature matrices, might be associated with the molecular structure of thiohydroxycarbene, suggesting that thiohydroxycarbene is not a true carbene, but, rather, a ylide with a negatively charged carbon atom and a positively charged sulfur atom (33).…”
Section: Discussionmentioning
confidence: 99%